Intellectual Capital Disclosure dan Kinerja Keuangan: Systematic Literature Review - Fadiyah, Nur Laily; Sabillah, Natasya; Islamiyah, Maya Adillah; Fernanda, Erfina; Hermawan, Sigit (Universitas Muhammadiyah Gresik, 2023)
This research aims to find out the direction of development of Intellectual Capital Disclosure and Financial Performance research for 7 years (2015-2022) by mapping or classifying according to themes and according to keywords. By using a literature review system as the basis for research analysis, this research uses a descriptive qualitative approach to collect data. The articles reviewed were taken from Sinta indexed or accredited Sinta-2 journal sources. The research results show: (1) Mapping according to theme shows that the Sinta 2 Accredited Scientific Journal with the name